2019
DOI: 10.1021/acsomega.9b03417
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Synthetically Versatile 2-Aminobenzophenones from Readily Accessed Acyl Hydrazides

Abstract: Herein, we report the transformation of readily accessed acyl hydrazides into protected 2-aminobenzophenones via a two-step process involving an aryne-based molecular rearrangement followed by a one-pot addition–elimination procedure. The assembly of the scaffold is tolerant of a wide variety of functional groups, and the carbamate group on the product can be facilely removed to afford highly valuable 2-aminobenzophenones. Application of the protocol was demonstrated in the synthesis of neurological medicine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Moreover, acridones were obtained from o -halobenzaldehyde hydrazones, the formation of which included an additional intramolecular S N Ar reaction and demethylation. Recently, Chudasama and co-workers reported a preparation of 2-hydrazobenzophenones 9-195 from arynes and readily achievable acyl hydrazides 9-194 (Scheme b). , Three plausible pathways were proposed for this transformation, all of which could lead to the formation of 9-195 . The 2-hydrazobenzophenone products 9-195 could be further converted to 1 H -/2 H -indazoles and 2-aminobenzophenones …”
Section: Cascade or Tandem Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, acridones were obtained from o -halobenzaldehyde hydrazones, the formation of which included an additional intramolecular S N Ar reaction and demethylation. Recently, Chudasama and co-workers reported a preparation of 2-hydrazobenzophenones 9-195 from arynes and readily achievable acyl hydrazides 9-194 (Scheme b). , Three plausible pathways were proposed for this transformation, all of which could lead to the formation of 9-195 . The 2-hydrazobenzophenone products 9-195 could be further converted to 1 H -/2 H -indazoles and 2-aminobenzophenones …”
Section: Cascade or Tandem Reactionsmentioning
confidence: 99%
“…The 2-hydrazobenzophenone products 9-195 could be further converted to 1H-/2H-indazoles 707 and 2aminobenzophenones. 708 In a study carried out by Wu, Sha, and co-workers on the reaction between 2-carboxylic acid ester substituted aziridines 9-196 and arynes, they found that indole spiro-derivatives 9-197 were obtained under anhydrous conditions (Scheme 193a). 591 Mechanistically, ammonium salt 9-198 could be formed via an aryne nucleophilic annulation reaction, which is then converted to 1-benzyl-2-methyleneindolin-3-ones 9-199 through ring-opening.…”
Section: Nucleophilic Annulation-induced Cascade Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of tetrabutylammonium difluorotriphenylsilicate (TBAT), the adduct 4a readily reacted with Kobayashi aryne precursor to provide the insertion product 8 in 84% yield, which could be further applied to the synthesis of the analogue of neurological medicine phenazepam. [ 17 ]…”
Section: Resultsmentioning
confidence: 99%